Performance of engineered cementitious composite (ECC) monolithic and composite slabs subjected to near-field blast. (15th March 2023) - Zhou, Hongyuan; Wu, Jiehao; Wang, Xiaojuan; Chen, Yu; Du, Xiuli; Yu, Shangjiang
Highlights: Performance of ECC monolithic and composite slabs under near-field blast was tested. ECC monolithic and composite slabs exhibited ductile response under near-field blast. No spalling occurred even ECC monolithic and composite slabs underwent large deformation and failed. Both ECC monolithic and composite slabs exhibited favorable performance under near-field blast. Abstract: To improve the performance of reinforced concrete (RC) structural members subjected to blast, especially the spalling due to the brittleness of concrete, engineered cementitious composite (ECC) was applied in monolithic and composite slabs and their responses subjected to near-field blast were experimentally investigated in the present study. First, two different ECC materials were prepared and tested with quasi-static direct tension and flexural tests, whose results showed significantly improved tensile ductility and strength compared to normal concrete. Then a field test was conducted to investigate the response of ECC monolithic and composite slabs under near field blast, with an RC slab as reference. The responses of these slabs were compared in terms of response mode, residual deformation, crack initiation and development, spalling, strain time history, etc. The test observations suggested that in addition to the ductile response and failure of ECC subjected to quasi-static direct tension and flexural tests, ECC still exhibited ductile response at high strain rate when applied in monolithic and composite slabs under near field blast. Compared to the perforation and spalling of RC slab, the ECC monolithic or composite slabs underwent large deformation, until collapse failure with a major crack in the mid-span occurred. Importantly, throughout the whole response process, even the ECC monolithic and composite slabs collapse with a major crack at mid-span, no spalling was observed. Furthermore, no delamination occurred in the interface between the RC and ECC layer of the RC/ECC slabs. Both the ECC monolithic slab and RC/ECC composite slab exhibited favorable performance subjected to near-field blast. These observations implied that the ECC is promising in the potential application of structural protection against blast, not only for replacing certain key components in the newly built structures but also for retrofitting existing RC structures.